Clinical efficacy and safety of rituximab in lupus nephritis - Zhong Z; Li H; Zhong H; Zhou T (Dove Medical Press, 2019)
Zhiqing Zhong,1,* Hongyan Li,2,* Hongzhen Zhong,1 Tianbiao Zhou1 1Department of Nephrology, The Second Affiliated Hospital, Shantou University Medical College, 515041 Shantou, China; 2Department of Nephrology, Huadu District People’s Hospital of Guangzhou, Southern Medical University, 510800 Guangzhou, China *These authors contributed equally to this work Background: Long-term treatment programs with low toxicity represent a therapeutic challenge in lupus nephritis (LN). Although a therapeutic benefit of rituximab (RTX) has been reported in LN patients who have failed conventional treatment, the results are controversial. We aimed to assess the clinical efficacy and safety of RTX as a new immunosuppressive medicine in the treatment of LN with a meta-analysis. Methods: Based on predetermined criteria, PubMed, Embase, and Cochrane Library were used to identify the eligible studies. Cochrane Review Manager version 5.3 was applied to pool the data extracted from individual investigations and provide summary effect estimates. Results: Twenty-four studies with 940 patients were analyzed. In case series trials with specific LN assessment, the complete remission (CR) rate at 12 months was 35.9% (95% CI: 24.2%–49.5%), and total remission (TR: CR plus partial remission) was 73.4% (95% CI: 66.0%–79.7%). In controlled trials, RTX was associated with a higher probability of TR (OR =2.02, 95% CI: 1.23–3.32, P<0.01). The CR in the RTX group was higher than that in the control group, although there was no significant difference between the two groups (OR =1.98, 95% CI: 0.90–4.39, P>0.05). Additionally, RTX treatment significantly decreased proteinuria (mean difference: -2.79, 95% CI: -3.95 to -1.62, P<0.01) as well as the renal activity index in patients with LN (mean difference: -3.46, 95% CI: -4.43 to -2.50, P<0.01). In controlled trials, the relative risks of the adverse events of infection and infusion reaction were not notably different between the two groups. Conclusion: RTX is a promising therapy for the treatment of LN due to significant clinical efficacy and a favorable safety profile. In future studies, larger study populations and longer-term time points may identify additional important patient-centered outcomes. Keywords: systemic lupus erythematosus, lupus nephritis, rituximab, efficacy, safety, meta-analysis